Hypoxia decreases the T helper cell-suppressive capacity of synovial fibroblasts by downregulating IDO1-mediated tryptophan metabolism - Kaul, Nathalie-Christin; Mohapatra, Soumya R.; Adam, Isabell; Tucher, Christine; Tretter, Theresa; Opitz, Christiane; Lorenz, Hanns-Martin; Tykocinski, Lars-Oliver (Rheumatology, 2020)
AbstractObjective. The development of RA is linked to local infiltration of immune cells and to changes in the phenotype of synovial fibroblasts. Synovial fibr
Advance access publication 17 December 2019
Gesehen am 17.07.2020